(3GdZQjHjfs - (3CMeO Hf eMeO Hf YHO GdQMef GdHGTGfj GdgQhj, CHh YHjO, J (B401 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdUGO HGH GdUGO eY GdgeRI s
(3BNQgG (B:s
(3jfJgi HHGH GdTjf eY GdjGA s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B210s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1209s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdMOjK h GdeUWdMs